Popularization of vegetable pigeonpea (Cajanus cajan) in central Gujarat through demonstration in farmers field - RAI, A K; KHAJURIA, S; LATA, K; JADAV, J K; RAJKUMAR, RAJKUMAR; KHADDA, B S (The Indian Journal of Agricultural Sciences, 2015)
Conventional pigeonpea [Cajanus cajan (L.) Millsp.] is harvested as seed but for the purpose of vegetable, it is harvested immature. At this stage it is a nutritious and delicious vegetable and forms a substitute for green pea (Pisum sativum L.). Pigeonpea is one of the most important pulse crops of the Panchmahals district of Gujarat. However, productivity of pigeonpea in the district is very low. Attempts were made to improve productivity and to increase area under pigeonpea by adopting high yielding varieties (HYVs). In order to compare conventional pigeonpea with HYVs, 75 front line demonstrations were carried out in systematic manner on farmers’ field to show the worth of new varieties in comparison to local check and thereby convincing farmers about potentialities of improved production management practices of pigeonpea for further adoption involving feasible and effective scientific package of practices. The demonstrations clearly showed on enhancement of productivity, simultaneously area under pigeonpea cultivation was also noticed to be increased. The yield (green pod) was found to be increased from 4 300 kg/ha in local check to 7 300 kg/ha in demonstrations. Similarly, the benefit cost ratio for HYVs was also increased to 3.22 as compared to local check (2.27). The economics and benefit cost ratio can be further improved to 3.23 when slightly higher inputs for cultivation and marketing. The impact of pigeonpea FLDs was analysed which showed improvement of knowledge and satisfaction of farmers as the main reason for mass scale adoption.